Analyzing the Link Between FOMO,Financial Literacy, and Financial Behavior in Shaping Entrepreneurial Intention Among Generation Z - Angelina Medina Najmani; I Gusti Bagus Yosia Wiryakusuma; Johan Pratama Siahainenia (Media Ekonomi dan Manajemen, 2026)
This study explores how FOMO, financial knowledge, and personal financial management habits shape entrepreneurial intention among Generation Z. Using a quantitative approach with SEM-PLS, the research examines the relationships among the key variables. The findings indicate that fear of missing out, financial literacy, and financial behavior each contribute to increasing young individuals’ inclination to engage in entrepreneurial activities. Financial literacy is shown to promote healthier financial behavior, which subsequently serves as an indirect pathway that enhances entrepreneurial intention. The study also reveals that financial literacy strengthens individuals’ responses to the influence of FOMO within the entrepreneurial context. Overall, the results illustrate that psychological factors and financial capabilities complement each other in fostering entrepreneurial interest. However, the study is limited by the dominance of student respondents, suggesting that future research should involve more diverse participant groups.